Place-Branded Foods with Responsible and Sustainable Management: A La Carte Serving in Regional Restaurants - Lopes, Celso (2022)
This study assesses whether the association of place-branded foods and the adoption of responsible and sustainable management practices (e.g., quality management, environmental management, and corporate social responsibility) influence the financial performance of regional restaurants linked to the land of origin. The data collected from 265 regional restaurants located in the Centre Region of Portugal allowed estimation of a selected set of discrete-choice model specifications, namely, probit, logit and generalised extreme value regression models. The empirical findings reveal that the use of place-branded foods increases the demand for regional restaurants, which positively influences their financial performance. In addition, responsible sustainable management practices such as collaboration with customers to improve products and services, quality and safety control, choice of organic foods, commitment to maintaining jobs and cooperation with the community reveal a positive and significant influence on financial performance. Conversely, the results show that the use of origin certification in marketing and advertising campaigns and improvement of the restaurant’s image through the use of place-branded products have a significantly negative influence on regional restaurants’ financial performance, considering the pandemic crisis and the additional costs associated with this differentiation procedure.